2006
DOI: 10.1074/jbc.m606449200
|View full text |Cite
|
Sign up to set email alerts
|

Airway Surface Liquid Volume Regulates ENaC by Altering the Serine Protease-Protease Inhibitor Balance

Abstract: Efficient clearance of mucus and inhaled pathogens from the lung is dependent on an optimal airway surface liquid (ASL) volume, which is maintained by the regulated transport of sodium and chloride across the airway epithelium. Accumulating evidence suggests that impaired mucus clearance in cystic fibrosis (CF) airways is a result of ASL depletion caused by excessive Na ؉ absorption through the epithelial sodium channel (ENaC). However, the cellular mechanisms that result in increased ENaC activity in CF airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
107
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(119 citation statements)
references
References 51 publications
9
107
3
Order By: Relevance
“…2 A). However, the serine proteases that activate ENaC are up-regulated in CF airway epithelia (10,40) and neutrophil elastase, which also activates ENaC, is increased in CF airways (41)(42)(43). Thus, it is possible that the excessive protease up-regulation seen in CF airways (10,40) interferes with the normal regulation of ENaC by SPLUNC1 and other potential ENaC regulators, and thus, shifts the balance from anti-proteases and less ENaC activity to a protease-replete state with more ENaC activity, overwhelming the ability of SPLUNC1 to inactivate ENaC and contributing to CF airway surface liquid volume depletion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 A). However, the serine proteases that activate ENaC are up-regulated in CF airway epithelia (10,40) and neutrophil elastase, which also activates ENaC, is increased in CF airways (41)(42)(43). Thus, it is possible that the excessive protease up-regulation seen in CF airways (10,40) interferes with the normal regulation of ENaC by SPLUNC1 and other potential ENaC regulators, and thus, shifts the balance from anti-proteases and less ENaC activity to a protease-replete state with more ENaC activity, overwhelming the ability of SPLUNC1 to inactivate ENaC and contributing to CF airway surface liquid volume depletion.…”
Section: Resultsmentioning
confidence: 99%
“…When human bronchial epithelial cultures are mounted in Ussing chambers where native airway surface liquid is washed away, ENaC is predominantly active, suggesting that cell attached proteases are predominant (8,9). In contrast, under thin film conditions, where native airway surface liquid is present, ENaC activity is reduced, suggesting that airway surface liquid contains soluble proteases inhibitors (10,11). Thus, based on the observation that diluting airway surface liquid with Ringer resulted in an increase in ENaC activity (10, 11), we speculated that unidentified protease inhibitors resided in the airway surface liquid.…”
mentioning
confidence: 99%
“…After the indicated period of time, the apical secretions were collected in 100 l of PBS and concentrated by acetone precipitation overnight; the basolateral medium was collected and similarly concentrated. After collection of the secretions, surface biotinylation and Western blotting were performed as previously described (34). Briefly, the HAEC cultures grown on filter supports were placed on ice, and the apical surface was washed with ice-cold PBS plus 1 mM CaCl 2 to remove cellular debris.…”
Section: Methodsmentioning
confidence: 99%
“…ENaC activity is increased in cystic fibrosis (CF), which, together with impaired CFTR-mediated anion secretion, leads to pathological ASL depletion and impaired mucus clearance from the lung (20, 23, 27, 29 -31, 41). Previous work from our group (34) and Tarran et al (42) has indicated that a balance between the protease activity of membrane-tethered channel-activating proteases (CAPs) and soluble protease inhibitors in the ASL modulates Na ϩ absorption in human airway epithelial cells (HAEC). When the ASL volume is low, as in the steady state, the soluble protease inhibitor concentration is sufficient to minimize constitutive activation of ENaC by CAPs in non-CF epithelium.…”
mentioning
confidence: 99%
See 1 more Smart Citation